Evaluating the Effect of Air Abrasive Polishing on Friction and Surface Micromorphology of Ceramic Brackets Using Different Wires - Ahmed R. Mohammed Hassan; Shahbaa A. Mohammed (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: The aim of this in vitro study was to evaluate the Resistance to Sliding (RS) provided by ceramic(Perfect clear) sapphire ceramic brackets using round 2 types of orthodontic wires (Fiber-Reinforced PolymerComposite (FRPC) and Epoxy fully coated Stainless-Steel), before and after the use of sodium bicarbonateairborne particle abrasion, in an experimental model with 3 non levelled brackets and to evaluate the surfacemicromorphology of these brackets by means of scanning electron microscopy.Materials and Methods: 0ne commercial brands of ceramic brackets were evaluated. The fourty specimenswere divided into two groups (n = 20) according to the two type of arch wires and each group was dividedinto four subgroup of five specimens according to the application or not of sodium bicarbonate airborneparticle abrasion for (5, 10 and 20) seconds. A device adapted to a universal testing machine was used tosimulate the movement of retraction in sliding mechanics, measuring the traction force needed to slide 10mm of the wire over the test specimen brackets. The test speed was 5 mm/min. The data were analyzed bytwo-way analysis of variance (ANOVA) and Tukey test.Conclusions: It may be concluded that it is not recommended to apply airborne particle abrasion on the slotsof ceramic.